Silhouettes of tango in the soundscape of Argentina: Astor Piazzolla’s music for solo guitar - Filatova, Tetiana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study lies in the consideration of Astor Piazzolla’s music for solo guitar from the perspective of the historical interaction of Argentine tango genre traditions, taking into account versions of its stylistic renewal in the composer’s work. The main objective of the study is to identify authentic genre features of tango in the context of its stylistic reconstruction in Astor Piazzolla’s work, using the example of the cycle ‘Five Pieces for Guitar’ and taking into account idiomatic performance borrowings. The novelty of the article lies in introducing genre and style analysis of the work into Ukrainian musicology in the context of connections with the timbral sonotypes of local soundscapes, performance techniques for imitating the sound of other instruments, and the interaction of the language of music with the poetics of dance movement. The methodology is based on an interdisciplinary approach and methods of historicaltheoretical, systemic, structural-functional analysis applied to determine the linguistic specificity of Argentine tango, the interaction of dance gestures with the metrorhythmic patterns of music, the influence of the stylistic features of the composer’s work, and folk and academic guitar performance techniques. Results and conclusions. The specificity of the analytical approach lies in correlating the archetype of tango with the characteristics of the sonotype of Argentina’s soundscapes and the timbral resources of archaic and modern instruments of various ethnic origins. The connections between the musical poetics of the genre and the plasticity of choreographic movement, which has Iberian and African-American roots and also depends on the articulation of accentual rhythms consistent with the local Spanish dialect of the inhabitants of Buenos Aires, are analysed. The cycle ‘Five Pieces for Guitar’ reveals the instrumental idioms of tango in solo performance thanks to special effects that imitate the timbres of other voices in the ensemble with the sounds of the guitar. The connections between each of the pieces in the cycle and the metrorhythmic features of milonga and Cuban habanera are highlighted. Connotations with European genre foundations of thematicism are emphasised, as well as conventional visualisations of typical tango characters in the characteristic emotional atmosphere of the dance. The influences of jazz musical vocabulary and elements of contemporary academic thinking are summarised. Guitar techniques and performance methods, melodic, harmonic, and rhythmic elements of the musical language of folk, academic, and nonacademic traditions appear as a set of integral attributes of the genre and style projections of Astor Piazzolla’s tango nuevo music, aimed at the depths of national sound mythologems.